PENGEMBANGAN VARIASI LATIHAN PASSING ATAS PERMAINAN BOLAVOLI DALAM KEGIATAN EKSTRAKURIKULER DI SMPN 21 MALANG - Faizal Dwi Hermawan; M. E. Winarno; Agus Tomi (Fakultas Ilmu Keolahragaan UM)
ABSTRACT: Passing over the volleyball game is one of the basic techniques that must be mastered. The material passing over the participants of extracurricular activities are less mastered volleyball games and practice passing techniques over the less varied, requiring the development of a variety of exercises passing over the. This research aims to develop product variations over the passing drills. The study uses a conceptual model and research subjects include subject matter experts and the subject of potential users. Of the test results by using a small group of 10 participants showed 86.70% and continued to test large groups by using the 30 participants showed 89.25%. Conclusion The results of this study indicate that the products developed by researchers and appropriate use. Key word: variations in practice, passing up, extracurricular activities